Morphometric Differences between Male and Female Fish Oxyurichthys Tentacularis, Gobiidae (Valenciennes, 1837) from Ashtamudi Lake- Kollam, Kerala - Mohan, Remya; E, Sherly Williams. (Asian Journal of Biological and Life Sciences, 2016)
The Oxyurichthys tentacularis, locally known as Koozhali, of the family Gobiidae is one of the important food fish of Ashtamudi lake. it is the first study, about morphometric differences between male and female fish species O. tentacularis, in Ashtamudi lake. Considering the commercial importance of this species, the objective of this study was to assess the morphometric features of male and female fish Oxyurichthys tentacularis. The study revealed that, the following morphometric characters between male and female showed significant differences as body width , body depth , head length, head width, pre pectoral fin length, dorsal fin length I, dorsal fin length II, dorsal fin base I, dorsal fin base II, pelvic fin length, pelvic fin base, pelvic fin width, caudal fin length, pectoral fin length, pectoral fin width, pectoral fin base, anal fin length, lower jaw length and maxilla length (t – test; P<0.01).. Caudal peduncle length exhibited significant difference at 5% level (t – test; P<0.05). Hence, these morphometric characters had been found to be helpful in observing the phenotypic variation among the male and female populations of this species.
Keywords: Female fish; Koozhali; Morphometric differences